2022
DOI: 10.3126/nmcj.v24i1.44139
|View full text |Cite
|
Sign up to set email alerts
|

Ocular manifestations and its associated factors in patients with dermatitis at a tertiary care hospital in Kathmandu

Abstract: Dermatitis also known as eczema, is inflammation of the skin, typically characterized by itchiness, redness and a rash. Dermatitis was estimated to affect 245 million people globally in 2015 or 3.34% of the world population. In Nepal, studies from different parts of the country have reported the prevalence of dermatitis between 15.9 to 39.2%. Severe dermatitis with repeated scratching and rubbing of the face predisposes the patient to various ocular complications. A hospital-based, cross-sectional, descriptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This study aims to bridge this research gap by conducting a thorough evaluation of patient satisfaction levels among those receiving services at the Outpatient Department of Nepal’s government-run tertiary care Mental Hospital. The findings of this research hold the potential not only to illuminate the patient experience within tertiary care public hospitals but also to contribute to the broader global discourse on enhancing healthcare service quality [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study aims to bridge this research gap by conducting a thorough evaluation of patient satisfaction levels among those receiving services at the Outpatient Department of Nepal’s government-run tertiary care Mental Hospital. The findings of this research hold the potential not only to illuminate the patient experience within tertiary care public hospitals but also to contribute to the broader global discourse on enhancing healthcare service quality [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic retinopathy (DR) is the leading cause of visual impairment among working aged individuals in both western worlds as well as in Nepal. [1][2][3][4] Detailed understanding of the prevalence of Diabetes Mellitus (DM), as well as the association of DR with other detectable conditions allows for improved awareness, screening and treatment, and subsequently lower incidence and severity of vision loss. [1][2][3][4] Previous population-based screening studies from Nepal have shown a higher percentage prevalence of DR than India.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Detailed understanding of the prevalence of Diabetes Mellitus (DM), as well as the association of DR with other detectable conditions allows for improved awareness, screening and treatment, and subsequently lower incidence and severity of vision loss. [1][2][3][4] Previous population-based screening studies from Nepal have shown a higher percentage prevalence of DR than India. 4 Different community based screening for DR found a prevalence of 19.3%, 5 and a subsequent community-based study in two different metropolitan cities of Nepal reported a slightly lower DR prevalence of approximately 12%.…”
Section: Introductionmentioning
confidence: 99%